ANALISIS PERBANDINGAN PENGUJIAN EKSPERIMENTAL DAN SIMULASI KOMPOR SURYA TIPE KOTAK UNTUKMEMASAK NASI DENGAN ERYTHRITOL SEBAGAI PCM - Gunawan, Safri; Rina, Wilda; Lubis, Abdi Bimardotillah (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
The use of solar energy can be converted to thermal energy and can be used for cooking, drying agricultural products, and heating water. Solar energy developed and converted into thermal energy for cooking is the solar cooker. This study aims to compare the results of experimental research with ANSYS 14.0 simulation when cooking rice on a solar cooker. The type of solar stove used is a box type by adding mirror as a reflector, copper vessel as a PCM container, lug to hold the vessel's position during the cooking process, and aluminum vessel as a container for cooking rice. The result shows that the errors occurred between experimental and simulation at 10 minutes, 60 minutes, 120 minutes and 360 minutes are 1.15%, 0.84%, 0.79%, and 0.56 %, respectively Keyword: Solar Energy, Solar Cooker, Ansys Simulation